Electrochemical Hardness: A Reactivity Descriptor for the Electrocatalytic Activity of mn4 Molecular Catalysts for the Reduction of o2 in Aqueous Media - Zagal-Moya, J; Zagal-Moya, J; Ponce-Hormazabal, I (Elsevier B.V., 2026)
Molecular catalysts, like metal complexes such as MN4 or MNx molecular catalysts exhibit several reactivity descriptors: (i) the M−O2 binding energy, (ii) the M(III)OH/(II) formal potential, (iii) the number of d-electrons in the MN4, (iv) the donor (M)-acceptor intermolecular hardness, and (v) π-electron graphene-MN4 delocalization factor. When oxygen reduction reaction (ORR) activity, expressed as (log j)E at constant potential, is plotted versus adsorption energy (Ead) or versus the formal potential E°’M(III)/(II), the trends exhibit symmetrical volcano correlations. In this work, we consolidate and extend the concept of electrochemical hardness (ΔEh) as a reactivity descriptor for MN4 molecular catalysts. This descriptor is defined as the potential separation between the two central formal potentials exhibited by surface-anchored MN4 molecular catalysts in the absence of O2 in aqueous media. The catalytic activity for ORR increases as ΔEh decreases, suggesting that for highly active catalysis, the two redox one-electron reversible processes tend to a minimum or even overlap. All these reactivity descriptors are not independent from each other and are closely related. © 2025